The impact of serotonin receptor 1A and 2A gene polymorphisms and interactions on suicide attempt and suicide risk in depressed patients with insufficient response to treatment – a European multicentre study. (January 2016) - Höfer, Peter; Schosser, Alexandra; Calati, Raffaella; Serretti, Alessandro; Massat, Isabelle; Kocabas, Neslihan A.; Konstantinidis, Anastasios; Mendlewicz, Julien; Souery, Daniel; Zohar, Joseph; Juven-Wetzler, Alzbeta; Montgomery, Stuart; et al.
Abstract : So far, associations between serotonergic neurotransmission pathways and suicidality have been reported. The aim of our study was to investigate the role of genetic polymorphisms and gene–gene interactions of the 5-HTR1A and the 5-HTR2A gene on suicide risk and/or a personal history of suicide attempts. A total of 374 major depressive disorder patients, adequately treated with antidepressants for at least 4 weeks, were collected in the context of a European multicentre study on treatment-resistant depression. We assessed suicidality using the Mini International Neuropsychiatric Interview and the Hamilton Rating Scale for Depression (HAM-D). Treatment response was defined as HAM-D⩽17 and remission as HAM-D⩽7 after 4 weeks of adequate antidepressant treatment. The 5-HTR1A rs6295 (C-1019G) single nucleotide polymorphism (SNP) and the 5-HTR2A rs7997012, rs6313, rs643627 and rs17288723 SNPs were selected for genotyping. Using logistic regression analyses, no association ( P <0.05) could be found between any SNP and neither suicide risk nor personal history of suicide attempts. Interactions between 5HTR1A rs6295 and 5HTR2A rs6313 in suicide risk, and 5HTR1A rs6295 and 5HTR2A rs643627 in a personal history of suicide attempts have been reported ( P =0.027 and 0.036, respectively); however, the results did not survive multiple testing correction. In conclusion, our study shows no association between 5HTR1A or 5HTR2A gene polymorphisms and both current suicide risk and personal history of suicide attempts. In addition, epistatic effects of 5HTR1A and 5HTR2A genes on suicidal behaviour were not significant, although sample size limitations do not allow definitive conclusions.